Strategi adaptasi arsitektural pada rumah usaha di Jalan Tubagus Ismail, Bandung (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Architectural adaptation strategy of shophouses in Jalan Tubagus Ismail, BandungThe area in Jalan Tubagus Ismail, Bandung is a lush residential area that now has turned into a commercial area. In this area, many shophouses grow and develop spontaneously and responsively due to the presence of students from top educational institutions in Bandung City. The intensification of activities and the high demand of basic needs from resident students have resulted in various architectural adaptation strategies carried out by shophouse owners based on their perceptions, powers, and desires. This study aims to identify the architectural adaptation strategies of shophouses in Jalan Tubagus Ismail. The study was conducted using qualitative research method through spatial practice and representational space approach. The result of this study shows that there is a tendency of architectural adaptation strategies in terms of consideration of the suitability between types of business and location, space layout, building facade, and provision of shared facility. Economic force plays important role in the adaptation strategies, even though it is also found that the balance between economic desire and need for dwelling still exists. The study of adaptive architectural strategy is expected to be able to contribute on socio-spatial relation in architecture through socio-spatial practice and representational space.
Keywords: Architectural adaptation strategy; Residential area; Shophouses; Socio-spatial practice